2013
DOI: 10.1097/mca.0b013e328361a942
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stress hyperglycemia on in-hospital stent thrombosis and prognosis in nondiabetic patients with ST-segment elevation myocardial infarction undergoing a primary percutaneous coronary intervention

Abstract: In nondiabetic patients with STEMI undergoing p-PCI, the patients with SH experienced a significantly higher incidence of mortality, ST, and composite MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…Although, to the best of our knowledge, no one has previously reported on the impact of perioperative hyperglycemia on microvascular thrombosis in human studies, Colen and colleagues demonstrated that streptozotocin‐induced hyperglycemic rats undergoing anastomosis of the femoral vessels had increased rates of thrombosis. Additionally, multiple studies have demonstrated increased rates of thrombotic complications in patients from other hyperglycemic surgical populations . McGirt et al found increased rates of myocardial infarction, CVA, and transient ischemic attacks in patients with hyperglycemia undergoing carotid endarterectomy that occurred independent of preexisting cardiac disease or a diagnosis of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Although, to the best of our knowledge, no one has previously reported on the impact of perioperative hyperglycemia on microvascular thrombosis in human studies, Colen and colleagues demonstrated that streptozotocin‐induced hyperglycemic rats undergoing anastomosis of the femoral vessels had increased rates of thrombosis. Additionally, multiple studies have demonstrated increased rates of thrombotic complications in patients from other hyperglycemic surgical populations . McGirt et al found increased rates of myocardial infarction, CVA, and transient ischemic attacks in patients with hyperglycemia undergoing carotid endarterectomy that occurred independent of preexisting cardiac disease or a diagnosis of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al examined the results of 853 patients who were treated by primary PCI for STEMI without DM. Patients with admission serum glucose over 180 mg/dL experienced a significantly higher incidence of mortality, stent thrombosis and composite MACE, and these findings correlate with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated glucose level during stress is a consequence of sympathetic nervous system activity and overproduction of catecholamines and cortisol, which encourage processes of gluconeogenesis, glycogenolysis, and lipolysis. 21 Zhang et al 22 examined the results of 853 patients who were treated by primary PCI for STEMI without DM. Patients with admission serum glucose over 180 mg/dL experienced a significantly higher incidence of mortality, stent thrombosis and composite MACE, and these findings correlate with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In PPCI-treated STEMI patients, SH is a marker of both subsequent mortality and more frequent major ad-verse cardiac and cerebrovascular events (MACE) in general [82][83][84] . SH was also associated with increased 30-day rates of reinfarction, acute renal injury, target vessel revascularization (TVR) and major bleeding in 3,405 patients in the HORIZONS-AMI trial 15 .…”
Section: Stress Hyperglycemia and The Major Adverse Cardiac And Cerebmentioning
confidence: 99%
“…Zhang et al 84 studied 853 STEMI patients. Inhospital stent thrombosis was also more commonly seen in patients with SH.…”
Section: Stress Hyperglycemia and The Major Adverse Cardiac And Cerebmentioning
confidence: 99%